2020
DOI: 10.1128/mbio.00949-20
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insight into TdfH-Mediated Zinc Piracy from Human Calprotectin by Neisseria gonorrhoeae

Abstract: Neisseria gonorrhoeae, responsible for the sexually transmitted infection gonorrhea, is an obligate human pathogen exquisitely adapted for survival on mucosal surfaces of humans. This host-pathogen relationship has resulted in evolution by N. gonorrhoeae of pathways that enable the use of host metalloproteins as required nutrients through the deployment of outer membrane-bound TonB-dependent transporters (TdTs). Recently, a TdT called TdfH was implicated in binding to calprotectin (CP) and in removal of the bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“…Due to its role in nutritional immunity through its ability to sequester Zn 2+ , CALP has become a target for zinc piracy by certain bacterial species much as LTF has. The TdfH protein of Neisseria gonorrhoeae binds to and extracts a zinc ion from human calprotectin (Kammerman et al 2020 ; Stork et al 2013 ) or the closely related psoriasin/S100A7 (Maurakis et al 2019 ). Likewise, Salmonella typhimurium employs a similar strategy, using the zinc transporter ZnuABC to sequester Zn 2+ away from CALP (Liu et al 2012 ).…”
Section: Regulation Of Zn 2+ -Dependent Proteins A...mentioning
confidence: 99%
“…Due to its role in nutritional immunity through its ability to sequester Zn 2+ , CALP has become a target for zinc piracy by certain bacterial species much as LTF has. The TdfH protein of Neisseria gonorrhoeae binds to and extracts a zinc ion from human calprotectin (Kammerman et al 2020 ; Stork et al 2013 ) or the closely related psoriasin/S100A7 (Maurakis et al 2019 ). Likewise, Salmonella typhimurium employs a similar strategy, using the zinc transporter ZnuABC to sequester Zn 2+ away from CALP (Liu et al 2012 ).…”
Section: Regulation Of Zn 2+ -Dependent Proteins A...mentioning
confidence: 99%
“…Other investigators have focused on intrinsic mechanisms important for N. gonorrhoeae survival. One such mechanism is the outer-membrane bound TonB -dependent transporters (TdTs) that N. gonorrhoeae use for uptake of metalloproteins from hosts [ 129 ]. Kammerman et al found that one specific TdT, TdfH , was found to be highly conserved in Neisseria species, making this an ideal target for antimicrobial therapy [ 129 ].…”
Section: Treatment Of N Gonorrhoeaementioning
confidence: 99%
“…One such mechanism is the outer-membrane bound TonB -dependent transporters (TdTs) that N. gonorrhoeae use for uptake of metalloproteins from hosts [ 129 ]. Kammerman et al found that one specific TdT, TdfH , was found to be highly conserved in Neisseria species, making this an ideal target for antimicrobial therapy [ 129 ]. A separate highly conserved component of N. gonorrhoeae is a multicomponent protein complex (BAM) critical to the synthesis of β-barrel outer membrane proteins [ 130 ].…”
Section: Treatment Of N Gonorrhoeaementioning
confidence: 99%
“…As generation of a nonbinding Ngo TbpA appears possible, using it as an immunogen to test protection relative to the wildtype may be a promising way forward. Indeed, as researchers gain more insight into other TdT/host protein pairs ( Jean et al., 2016 ; Maurakis et al., 2019 ) and further characterize TdT structures and binding propensities ( Sikora et al., 2018 ; Yadav et al., 2019 ; Kammerman et al., 2020 ), similar studies with the other TdTs are feasible.…”
Section: Tonb-dependent Transportersmentioning
confidence: 99%